Acid-Catalyzed Ring-Opening Cyclization of Spirocyclopropanes for the Construction of a 2-Arylbenzofuran Skeleton: Total Synthesis of Cuspidan B - Nambu, Hisanori; Ono, Naoki; Yakura, Takayuki (Synthesis, 2016)
Acid-catalyzed ring-opening cyclization of cyclohexane-1,3-dione-2-spirocyclopropanes under metal-free conditions proceeded smoothly at room temperature to provide 2-aryl-3,5,6,7-tetrahydro-1-benzofuran-4(2H)-ones in excellent yields without the formation of 3-substituted isomers. The obtained product was converted into a 2-arylbenzofuran derivative via a synthetically useful 2-aryl-2,3-dihydrobenzofuran intermediate. Furthermore, the first total synthesis of cuspidan B was achieved by using the present method.
Keywords: cyclopropanes; benzofurans; natural products; ring opening; cyclization; total synthesis